2020
DOI: 10.1055/s-0040-1714194
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Coconut Oil in Treating Patients Affected by Plaque-Induced Gingivitis: A Pilot Study

Abstract: Objectives The aim of the study was to evaluate the coconut oil pulling efficacy as adjuvant in reducing plaque formation and in treating plaque-induced gingivitis. Materials and Methods A sample of 20 patients was divided into two groups: a study and a control group. In the study group, coconut oil, in form of mouthwash, was administered to a sample of patients affected by gingivitis, aged between 18 and 35. The protocol established a daily application of the product for 30 days, where clinical parameters for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…This reaction reduces the binding probability of bacterial plaque to surfaces. (21) According to studies by Beenashino et al, (4) Peedikayil et al, (7) and Ogbolu et al, (3) coconut oil has an inhibitory effect on Candida albicans, Staphylococcus aureus, and Escherichia coli, which was inconsistent with the present results. This discrepancy may be due to the difference in the type of bacteria since A. actinomycetemcomitans which is a Gram-negative microorganism was evaluated in the present study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This reaction reduces the binding probability of bacterial plaque to surfaces. (21) According to studies by Beenashino et al, (4) Peedikayil et al, (7) and Ogbolu et al, (3) coconut oil has an inhibitory effect on Candida albicans, Staphylococcus aureus, and Escherichia coli, which was inconsistent with the present results. This discrepancy may be due to the difference in the type of bacteria since A. actinomycetemcomitans which is a Gram-negative microorganism was evaluated in the present study.…”
Section: Discussioncontrasting
confidence: 86%
“…(6) Also, a control-free clinical trial showed that topical application of coconut oil led to a reduction in inflammation and plaque index in patients with plaque-free gingivitis. (7) coconut water, the coconuts were cracked and water was drained. Oil extraction was carried out at a temperature of -50°C using a coconut oil extraction machine under a cold pressing process (Iran Cold Pressing Co., 35 caliber model, Iran).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kaliamoorthy et al (2018)showed coconut oil gargling showed a significant reduction in the severity of gingivitis in the coconut oil group than the sesame oil group at all postintervention stages of their study. In the latest study by Ripari et al (2020), coconut oil pulling showed a significant decrease in reducing plaque formation and gingivitis. The results of these studies are in agreement with our study results.…”
Section: Discussionmentioning
confidence: 96%
“…Oil rinsing is a type of traditional procedure in the Indian system of medicine that involves swishing edible oil in the mouth and then spitting it out. This procedure is also called 'Oil Pulling' because the oil used for swishing is pulled and swirled to all parts of the oral cavity by movements of the tongue and oral musculature (Ripari et al, 2020). Ancient Ayurveda textbooks like Charaka Samhita and Arthashastra have mentioned these procedures as Kavala Gandoosha and Kavala Graha.…”
Section: Introductionmentioning
confidence: 99%
“…The process of making VCO can be carried out in 2 ways, namely, VCO from fresh coconut flesh, known as the wet process because in this process, water is added to extract oil, while the manufacture of VCO with raw copra is known as the dry process [ 2 4 ]. The heating process in the manufacture of VCO produces compounds containing lauric acid, so they have antibacterial properties [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%